Preparation method of dry-method pole piece

By using the structure of a conductive grid and a dry self-supporting film in the preparation of dry electrode sheets, combined with the use of modified adhesives, the problems of easy material dropping and poor electrical performance of the existing dry electrode sheets are solved, and higher electrical performance and cycle stability are achieved.

CN119864375AActive Publication Date: 2025-04-22JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510138669.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-22
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

In the existing dry electrode sheet preparation method, insufficient fibrillation effect of the adhesive causes the electrode sheet to fall off easily, insufficient compaction density affects the charging and discharge performance and cycle life of the battery, and poor electrical performance is not suitable for large-scale discharge and cycleability.

Method used

The conductive bonding net is formed by sputtering an adhesive on the conductive network, and the active material, conductive agent and adhesive are mixed and rolled into a dry self-supporting film, and then unrolled and rolled with the current collector and the conductive bonding net to form an optimized dry-like electrode structure.

Benefits of technology

The self-generating cohesion and bonding force of the dry electrode sheet are improved, the electrical performance (internal resistance, magnification, circulation) and cycling stability of the battery are enhanced, and the problems of material dropout and poor electrical performance are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864375A_ABST
    Figure CN119864375A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a preparation method of a dry-method pole piece. Comprising the following steps: step 1, sputtering a layer of binder on a conductive net to obtain a conductive bonding net; 2, mixing an active material, a conductive agent and a binder, and rolling to obtain a dry-process self-supporting film; and 3, simultaneously unwinding the current collector, the conductive bonding net and the dry-method self-supporting film, rolling and compounding to obtain the dry-method pole piece. The bonding force between the self-supporting film and the fluid can be better increased; the problems that the fibrillation effect of an adhesive is insufficient, and a pole piece falls off in the treatment process are solved; the conductive network connection area of the dry-method pole piece is increased, and the conductivity is better; the binding power of the dry-method pole piece is increased, so that the cycle life of the battery is longer; and the problems of pole piece material falling and pole piece breakage of the dry-method pole piece at a high curl rate are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for preparing a dry-process electrode. Background Art

[0002] With the continuous development and widespread application of lithium-ion battery technology, higher and higher requirements are placed on the performance and safety of lithium-ion batteries. As an important component of the battery, the preparation method and quality of the pole piece of the lithium-ion battery directly affect the overall performance and life of the battery.

[0003] In the prior art, dry powder preparation usually undergoes a pre-pressing and a secondary die-casting to form an active layer, which is then directly compounded with a current collector to produce a dry-process electrode. However, there are many challenges and problems in this process. In the dry process, the fibrillation effect of the adhesive is the core link in constructing a self-supporting membrane. If the fibrillation effect of the adhesive is not fully demonstrated, the electrode will easily fall off in the subsequent processing flow, thereby affecting the overall quality and performance of the electrode.

[0004] In addition, dry electrodes also face the challenge of insufficient compaction density during the compaction process. If the compaction density is not enough, the contact between the particles is not close, which can easily lead to material falling, thus affecting the charge and discharge performance and cycle life of the battery. What is more complicated is that in the preparation process of dry electrodes, improper equipment operation may also be a cause of material falling. For example, in the processes of unloading, chopping, crushing, screening and sorting, if not handled properly, it may lead to the loss of active substances and the destruction of the electrode structure, leading to material falling. At the same time, the electrical properties of the dry electrode prepared by the prior art are poor, and are not suitable for high-rate discharge and cyclability, which to a certain extent limits the application of dry electrode in the field of high-performance lithium-ion batteries.

[0005] In summary, it is of great significance to obtain a method for preparing dry-process electrodes. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a dry-process electrode to solve the problems raised in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a dry electrode comprises the following steps: Step 1: sputtering a layer of adhesive on the conductive mesh to obtain a conductive adhesive mesh; Step 2: Mix the active material, the conductive agent and the binder, and roll them to obtain a dry self-supporting film; Step 3: Unwind the current collector, the conductive adhesive mesh, and the dry process self-supporting film simultaneously, and roll-combine them to obtain a dry process electrode.

[0008] More optimally, the structure of the dry-process electrode includes a dry-process self-supporting film, a conductive adhesive mesh, a current collector, a conductive adhesive mesh, and a dry-process self-supporting film from top to bottom; the thickness of the conductive mesh in the dry-process electrode is 5~7um, and the layer thickness formed by the adhesive is ≤1um.

[0009] Preferably, the conductive mesh is made of at least one of metal, carbon material and polymer material.

[0010] More optimally, the rolling of the dry self-supporting film includes two rolling steps, the first rolling pressure is 1-10 tons, and the thickness after rolling is 300-4000 μm; the second rolling pressure is 15-100 tons, and the thickness after rolling is 150-2000 μm.

[0011] More optimally, the roller-compression compounding pressure is 25-40T.

[0012] More optimally, the raw materials of the dry self-supporting film include the following components: by mass percentage, 94% to 95% active material, 2% to 3% conductive agent, and 3% binder.

[0013] In the present application, the dry electrode is a dry positive electrode. Correspondingly, the raw materials of the dry self-supporting film include active materials but are not limited to 911NCM, and the conductive agent includes but is not limited to conductive carbon black SP; the raw materials of the binder include one or two of polytetrafluoroethylene and polyvinylidene fluoride.

[0014] In the more optimized solution, the active material is 94~95% 911NCM, the conductive agent is 2~3% conductive carbon black SP, and the binder is 2% PTFE (polytetrafluoroethylene) and 1% PVDF (polyvinylidene fluoride).

[0015] In addition, it should be noted that the relevant methods for dry-process electrodes in the present application are suitable for preparing dry-process negative electrodes; accordingly, when used for dry-process negative electrodes, the more optimized active material in the raw materials of the dry-process self-supporting membrane is SiC (C: 90%, Si: 10%).

[0016] In a further solution, the binder is further modified and optimized, specifically: the preparation method of the binder is: Step 1: Under a nitrogen atmosphere, add polytetrafluoroethylene and sodium naphthalene activation solution to dimethylformamide, react at 20-30° C. for 3-10 minutes, wash and filter to obtain pretreated polytetrafluoroethylene; Step 2: adding pretreated polytetrafluoroethylene, acrylic acid, acrylamide, (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, hydroxyethyl acrylate, ammonium persulfate, and allyltrimethoxysilane to a deionized water-acetone mixed solvent, reacting at 50-70° C. for 4-5 hours, then cooling to 20-30° C. and stirring for 1-2 hours, washing, and filtering to obtain modified polytetrafluoroethylene; Step 3: Mix the modified polytetrafluoroethylene, oxalic acid, phenol and formaldehyde at 60-95°C for 3-4 hours, cool to 35-45°C, and then dry at 80-130°C for 1-2 hours, add 8-12 wt% of hexamethylenetetramine, crush and grind to obtain composite polytetrafluoroethylene powder; Step 4: Evenly mix the composite polytetrafluoroethylene powder, polyvinylidene fluoride and carboxymethyl cellulose to obtain a binder.

[0017] More optimally, the raw materials of the modified polytetrafluoroethylene include, by weight, 4 to 5 parts of pretreated polytetrafluoroethylene, 4 to 5 parts of acrylic acid, 2 to 3 parts of acrylamide, 6 to 8 parts of (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, 3 to 4 parts of hydroxyethyl acrylate, 0.2 to 0.5 parts of ammonium persulfate, 4 to 5 parts of allyltrimethoxysilane, and 45 to 55 parts of a deionized water-acetone mixed solvent; in the raw materials of the deionized water-acetone mixed solvent, the mass ratio of deionized water to acetone is 2 to 2.5:1; The raw materials of the composite polytetrafluoroethylene powder include, by weight, 5 to 6 parts of modified polytetrafluoroethylene, 0.2 to 0.4 parts of oxalic acid, 4 to 5 parts of phenol, 7 to 8 parts of formaldehyde, and 0.5 to 1 part of 8 to 12 wt% hexamethylenetetramine.

[0018] More optimally, in the raw materials of the binder, the mass ratio of composite polytetrafluoroethylene powder, polyvinylidene fluoride, and carboxymethyl cellulose is 1.7~2.3:1:1.

[0019] Among them, polytetrafluoroethylene is first activated, and then grafted with acrylic acid, acrylamide, (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, hydroxyethyl acrylate, and allyltrimethoxysilane under the condition of an initiator, and then the carboxyl and hydroxyl groups on the surface of the grafted modified polytetrafluoroethylene undergo esterification reaction to participate in the synthesis of phenolic resin to form a three-dimensional network structure, promote fibrillation, improve the overall bonding performance, thermal stability, heat resistance and mechanical properties of the binder, and more effectively guide the uniform distribution of active substances in the pole piece, thereby solving the problem of pole piece shedding during processing, further reducing the internal resistance of the battery, and improving the electrical performance and cycle stability.

[0020] In the scheme, after fibrillation, the bonding performance between the binder and the active material in the dry self-supporting film will be reduced, which will cause the active material to fall off and greatly affect the increase of the internal resistance of the battery, and the battery performance will be greatly reduced. In the scheme, the composite polytetrafluoroethylene powder is mixed with polyvinylidene fluoride and carboxymethyl cellulose at a small particle size to obtain a binder. Polyvinylidene fluoride and carboxymethyl cellulose are non-fibrillated materials, which can significantly improve the bonding force between the binder and the active material, thereby reducing the shedding of the active material. The binder with a smaller particle size not only enhances the adhesion, but also promotes the uniform distribution of the active material in the electrode film. This uniform distribution not only improves the energy density of the battery, but also makes the battery show more stable and reliable performance during the charging and discharging process.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) This scheme improves the self-generated cohesion and adhesion of dry-process electrodes.

[0022] (2) This scheme improves the curling rate and folding resistance of the dry-process electrode.

[0023] (3) This solution improves the electrical performance of the battery (internal resistance, rate, and cycle).

[0024] (4) This solution solves the process problems of dry-process electrode breakage, material dropout, etc.

[0025] (5) In the scheme, a three-dimensional network structure is formed by introducing a composite polytetrafluoroethylene powder binder, which enhances the fibrillation effect, thereby improving the overall bonding performance, thermal stability, heat resistance and mechanical properties of the binder. The problem of material shedding is solved, and the internal resistance of the battery is further reduced, and the electrical performance and cycle stability are improved. It is also mixed with non-fibrillated materials at a smaller particle size, which significantly improves the bonding force between the binder and the active material and reduces the shedding of the active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 The present invention is a roadmap for the preparation method of a dry electrode. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that the following parts are by mass, and all raw materials involved in the present invention are purchased from manufacturers without any special restrictions. Examples include: In the following embodiments, sodium naphthalene activation solution was purchased from Ark (Fogang) Chemical Material Co., Ltd.; acrylic acid was purchased from Shandong Langcheng Chemical Co., Ltd.; polytetrafluoroethylene was purchased from Wuhan Haorong Biotechnology Co., Ltd.

[0029] In the following embodiments, the structure of the dry-process electrode sheet includes, from top to bottom, a dry-process self-supporting film, a conductive adhesive mesh, a current collector, a conductive adhesive mesh, and a dry-process self-supporting film.

[0030] Embodiment 1: A method for preparing a dry electrode comprises the following steps: Step 1: sputtering a layer of adhesive on the conductive mesh to obtain a conductive adhesive mesh; wherein the conductive mesh is made of aluminum, the thickness of the conductive mesh is 5um, and the thickness formed by the adhesive is 1um; Step 2: By weight percentage, 94% active material (911NCM), 3% conductive agent (conductive carbon black SP), and 3% binder are mixed; the first rolling is performed at a rolling pressure of 5.5 tons, and the thickness after the first rolling is 1900 μm, and then the second rolling is performed at a rolling pressure of 57.5 tons, and the thickness after the second rolling is 1075 μm, to obtain a dry self-supporting film; Step 3: Unwind the current collector, the conductive adhesive mesh, and the dry process self-supporting film at the same time, and roll-combine them at a pressure of 33T to obtain a dry process positive electrode sheet; In this embodiment, the binders in step 1 and step 2 are both 2% PTFE and 1% PVDF.

[0031] Embodiment 2: A method for preparing a dry electrode comprises the following steps: Step 1: sputtering a layer of adhesive on the conductive mesh to obtain a conductive adhesive mesh; wherein the conductive mesh is made of aluminum, the thickness of the conductive mesh is 5um, and the thickness formed by the adhesive is 1um; Step 2: By weight percentage, 94% active material (911NCM), 3% conductive agent (conductive carbon black SP), and 3% binder are mixed; the first rolling is performed at a rolling pressure of 5.5 tons, and the thickness after the first rolling is 1900 μm, and then the second rolling is performed at a rolling pressure of 57.5 tons, and the thickness after the second rolling is 1075 μm, to obtain a dry self-supporting film; Step 3: Unwind the current collector, the conductive adhesive mesh, and the dry process self-supporting film at the same time, and roll-combine them at a pressure of 33T to obtain a dry process positive electrode sheet; In this embodiment, the preparation method of the binder in step 1 and step 2 is as follows: (1) under a nitrogen atmosphere, polytetrafluoroethylene and sodium naphthalene activation solution are added to dimethylformamide, reacted at 25° C. for 7 minutes, washed and filtered to obtain pretreated polytetrafluoroethylene; (2) 4.5 parts of pretreated polytetrafluoroethylene, 4.5 parts of acrylic acid, 2.5 parts of acrylamide, 7 parts of (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, 3.5 parts of hydroxyethyl acrylate, 0.3 parts of ammonium persulfate, and 4.5 parts of allyl trimethoxysilane are added to 50 parts of a deionized water-acetone mixed solvent, and heated at 60 ℃ for reaction for 4.5 hours, then cool to 25 ℃ and stir for 1.5 hours, wash and filter to obtain modified polytetrafluoroethylene; (3) 5.5 parts of modified polytetrafluoroethylene, 0.3 parts of oxalic acid, 4.5 parts of phenol and 7.5 parts of formaldehyde are mixed and reacted at 80 ℃ for 3.5 hours, cooled to 40 ℃, and then dried at 100 ℃ for 1.5 hours, 0.8 parts of 10wt% hexamethylenetetramine are added, crushed and ground to obtain composite polytetrafluoroethylene powder; (4) Composite polytetrafluoroethylene powder, polyvinylidene fluoride and carboxymethyl cellulose in a mass ratio of 2:1:1 are evenly mixed to obtain a binder.

[0032] Comparative Example 1: Dry electrode was prepared by using the existing technology, specifically: Step 1: By weight percentage, 94% active material (911NCM), 3% conductive agent (conductive carbon black SP), and 3% binder are mixed; the binder is the same as the binder in Example 2; and a raw material mixture is obtained; Step 2: pre-pressing the raw material mixture once, the pre-pressing pressure is 5.5 tons, to obtain a pre-formed active layer, the thickness of the pre-formed active layer is 1900 μm; Step 3: Perform secondary die casting on the preformed active layer at a pressure of 57.5 tons to obtain an active layer having a thickness of 1075 μm; Step 4: Thermally compound the active layer and the current collector to obtain a dry-process positive electrode sheet.

[0033] Comparative Example 2: Preparation of dry electrode using polytetrafluoroethylene as a binder, specifically: Step 1: By weight percentage, 94% active material (911NCM), 3% conductive agent (conductive carbon black SP), and 3% binder are mixed; the binder is a single polytetrafluoroethylene; and a raw material mixture is obtained; Step 2: pre-pressing the raw material mixture once, the pre-pressing pressure is 5.5 tons, to obtain a pre-formed active layer, the thickness of the pre-formed active layer is 1900 μm; Step 3: Perform secondary die casting on the preformed active layer at a pressure of 57.5 tons to obtain an active layer having a thickness of 1075 μm; Step 4: Thermally compound the active layer and the current collector to obtain a dry-process positive electrode sheet.

[0034] Comparative Example 3: Based on Example 2, composite polytetrafluoroethylene powder is used as a binder, and the other processes remain unchanged, except that: In this embodiment, the preparation method of the binder in step 1 and step 2 is as follows: (1) under a nitrogen atmosphere, polytetrafluoroethylene and sodium naphthalene activation solution are added to dimethylformamide, reacted at 25° C. for 7 minutes, washed and filtered to obtain pretreated polytetrafluoroethylene; (2) 4.5 parts of pretreated polytetrafluoroethylene, 4.5 parts of acrylic acid, 2.5 parts of acrylamide, 7 parts of (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, 3.5 parts of hydroxyethyl acrylate, 0.3 parts of ammonium persulfate, 4.5 parts of allyl trifluoroacetic acid, 1.5 parts of ethyl acrylate, 0.3 parts of ammonium persulfate, 1.5 parts of ethyl acrylate, 0.3 parts of propylene glycol, 0.5 parts of propylene glycol, 0.6 parts of propylene glycol, 0.7 parts of propylene glycol, 0.8 parts of propylene glycol, 0.9 parts of propylene glycol, 1.1 parts of propylene glycol, 0.9 ... Methoxysilane was added to 50 parts of a deionized water-acetone mixed solvent, reacted at 60°C for 4.5 hours, then cooled to 25°C and stirred for 1.5 hours, washed and filtered to obtain modified polytetrafluoroethylene; (3) 5.5 parts of modified polytetrafluoroethylene, 0.3 parts of oxalic acid, 4.5 parts of phenol and 7.5 parts of formaldehyde were mixed and reacted at 80°C for 3.5 hours, cooled to 40°C, then dried at 100°C for 1.5 hours, 0.8 parts of 10 wt% hexamethylenetetramine was added, crushed and ground to obtain a binder.

[0035] Comparative Example 4: Based on Example 2, the modified polytetrafluoroethylene is used instead of the composite polytetrafluoroethylene powder, and the other processes remain unchanged, except that: In this embodiment, the preparation method of the binder in step 1 and step 2 is as follows: (1) under a nitrogen atmosphere, polytetrafluoroethylene and sodium naphthalene activation solution are added to dimethylformamide, reacted at 25° C. for 7 minutes, washed and filtered to obtain pretreated polytetrafluoroethylene; (2) 4.5 parts of pretreated polytetrafluoroethylene, 4.5 parts of acrylic acid, 2.5 parts of acrylamide, 7 parts of (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, 3.5 parts of hydroxyethyl acrylate, 0.3 parts of ammonium persulfate, and 4.5 parts of allyltrimethoxysilane are added to 50 parts of a deionized water-acetone mixed solvent, reacted at 60° C. for 4.5 hours, then cooled to 25° C. and stirred for 1.5 hours, washed and filtered to obtain modified polytetrafluoroethylene; (3) modified polytetrafluoroethylene, polyvinylidene fluoride, and carboxymethyl cellulose in a mass ratio of 2:1:1 are uniformly mixed to obtain a binder.

[0036] Comparative Example 5, based on Example 2, does not add (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, and the other processes remain unchanged, except that: In this embodiment, the preparation method of the binder in step 1 and step 2 is as follows: (1) under a nitrogen atmosphere, polytetrafluoroethylene and sodium naphthalene activation solution are added to dimethylformamide, reacted at 25°C for 7 minutes, washed and filtered to obtain pretreated polytetrafluoroethylene; (2) 5 parts of pretreated polytetrafluoroethylene, 4.5 parts of acrylic acid, 2.5 parts of acrylamide, 3.5 parts of hydroxyethyl acrylate, 0.3 parts of ammonium persulfate, and 4.5 parts of allyltrimethoxysilane are added to 50 parts of a deionized water-acetone mixed solvent, reacted at 60°C for 4.5 hours, and then cooled to The mixture was stirred at 25°C for 1.5 hours, washed and filtered to obtain modified polytetrafluoroethylene; (3) 5.5 parts of modified polytetrafluoroethylene, 0.3 parts of oxalic acid, 4.5 parts of phenol and 7.5 parts of formaldehyde were mixed and reacted at 80°C for 3.5 hours, cooled to 40°C, and then dried at 100°C for 1.5 hours, 0.8 parts of 10 wt% hexamethylenetetramine were added, crushed and ground to obtain composite polytetrafluoroethylene powder; (4) Composite polytetrafluoroethylene powder, polyvinylidene fluoride and carboxymethyl cellulose in a mass ratio of 2:1:1 were evenly mixed to obtain a binder.

[0037] Testing experiment: The dry-process positive electrode sheets prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were subjected to performance testing; wherein, 1. The dry-process positive electrode sheets were cut into qualified laminates (size: coating area length 200 mm, width 150 mm, and the tab length 25 mm, width 50 mm on the basis of the tab); 2. The negative electrode sheet was 5 mm larger (width 155 film surface); 3. After the lamination process, hot pressing and cold pressing were performed to obtain a battery cell (tabs at both ends), and then a soft-pack battery was made and the electrical performance was tested. The test results are shown in Table 1;

[0038] Result analysis: According to the data analysis in Table 1, it can be seen that a dry-process electrode prepared by this scheme can better increase the adhesion between the self-supporting film and the fluid; it can solve the problem of insufficient fibrillation of the adhesive and the electrode falling off during the processing; it can increase the connection area of ​​the conductive network of the dry-process electrode and improve the conductivity; it can increase the adhesion of the dry-process electrode and make the battery cycle life longer; it can solve the problem of electrode falling off and electrode breakage damage of the dry-process electrode at a high curling rate.

[0039] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a dry electrode, characterized in that: The following steps are involved: Step 1: sputtering a layer of adhesive on the conductive mesh to obtain a conductive adhesive mesh; Step 2: Mix the active material, the conductive agent and the binder, and roll them to obtain a dry self-supporting film; Step 3: Unwind the current collector, the conductive adhesive mesh, and the dry process self-supporting film simultaneously, and roll-combine them to obtain a dry process electrode.

2. The method for preparing a dry electrode according to claim 1, characterized in that: The structure of the dry-process electrode includes a dry-process self-supporting film, a conductive adhesive mesh, a current collector, a conductive adhesive mesh, and a dry-process self-supporting film from top to bottom; the thickness of the conductive mesh in the dry-process electrode is 5~7um, and the layer thickness formed by the adhesive is ≤1um.

3. The method for preparing a dry electrode according to claim 1, characterized in that: The conductive mesh is made of at least one of metal, carbon material and polymer material.

4. The method for preparing a dry electrode according to claim 1, characterized in that: The rolling of the dry self-supporting film includes two rolling processes, the first rolling pressure is 1-10 tons, and the thickness after rolling is 300-4000 μm; the second rolling pressure is 15-100 tons, and the thickness after rolling is 150-2000 μm.

5. The method for preparing a dry electrode according to claim 1, characterized in that: The pressure of the roll-combination is 25-40T.

6. The method for preparing a dry electrode according to claim 1, characterized in that: The raw materials of the dry process self-supporting film include the following components: by mass percentage, 94% to 95% active material, 2% to 3% conductive agent, and 3% binder.

7. The method for preparing a dry electrode according to claim 1, characterized in that: The raw materials of the binder include one or two of polytetrafluoroethylene and polyvinylidene fluoride.

8. The method for preparing a dry electrode according to claim 1, characterized in that: The preparation method of the binder is: Step 1: Under a nitrogen atmosphere, add polytetrafluoroethylene and sodium naphthalene activation solution to dimethylformamide, react at 20-30° C. for 3-10 minutes, wash and filter to obtain pretreated polytetrafluoroethylene; Step 2: adding pretreated polytetrafluoroethylene, acrylic acid, acrylamide, (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, hydroxyethyl acrylate, ammonium persulfate, and allyltrimethoxysilane to a deionized water-acetone mixed solvent, reacting at 50-70° C. for 4-5 hours, then cooling to 20-30° C. and stirring for 1-2 hours, washing, and filtering to obtain modified polytetrafluoroethylene; Step 3: Mix the modified polytetrafluoroethylene, oxalic acid, phenol and formaldehyde at 60-95°C for 3-4 hours, cool to 35-45°C, and then dry at 80-130°C for 1-2 hours, add 8-12 wt% of hexamethylenetetramine, crush and grind to obtain composite polytetrafluoroethylene powder; Step 4: Evenly mix the composite polytetrafluoroethylene powder, polyvinylidene fluoride and carboxymethyl cellulose to obtain a binder.

9. The method for preparing a dry electrode according to claim 8, characterized in that: The raw materials of the modified polytetrafluoroethylene include, by weight, 4 to 5 parts of pretreated polytetrafluoroethylene, 4 to 5 parts of acrylic acid, 2 to 3 parts of acrylamide, 6 to 8 parts of (2E)-3-(6-amino-3-pyridyl)-2-acrylic acid, 3 to 4 parts of hydroxyethyl acrylate, 0.2 to 0.5 parts of ammonium persulfate, 4 to 5 parts of allyltrimethoxysilane, and 45 to 55 parts of a deionized water-acetone mixed solvent; in the raw materials of the deionized water-acetone mixed solvent, the mass ratio of deionized water to acetone is 2 to 2.5:1; The raw materials of the composite polytetrafluoroethylene powder include, by weight, 5 to 6 parts of modified polytetrafluoroethylene, 0.2 to 0.4 parts of oxalic acid, 4 to 5 parts of phenol, 7 to 8 parts of formaldehyde, and 0.5 to 1 part of 8 to 12 wt% hexamethylenetetramine.

10. The method for preparing a dry electrode according to claim 8, characterized in that: In the raw materials of the binder, the mass ratio of composite polytetrafluoroethylene powder, polyvinylidene fluoride and carboxymethyl cellulose is 1.7-2.3:1:1.

Citation Information

Patent Citations

  • Preparation method of solvent-resistant PTFE composite nanofiltration membrane

    CN114832653A

  • Dry-method electrode plate and preparation method and application thereof

    CN116314598A

  • Dry-method electrode film, preparation method and application thereof

    CN116885182A

  • Dry-method electrode pole piece processing method and dry-method electrode pole piece processing system

    CN118136786A

  • Preparation method of dry-method electrode

    CN118156431A